A diffractive analysis of a grade 10 art project conducted at the Tygerberg Art Centre situated in Parow, Cape Town - Kotze, Roline (Stellenbosch : Stellenbosch University, 2017)
Thesis MA(VA)--Stellenbosch University, 2017.